Comparative Homing Behaviors in Two Species of Crayfish, Fallicambarus Fodiens and Orconectes Rusticus. (6th May 2015) - Kamran, Maryam; Moore, Paul A.; Koenig, W.
Abstract Homing behaviors are seen across the animal kingdom, with the magnitude and scale of these movements varying to a great degree. Invertebrates, such as crayfish, prove to be excellent models for comparative research, with relatively simple nervous systems that have been extensively studied combined with a rich behavioral repertoire that has been well documented. Here we explore whether two crayfish species (a primary burrower and a tertiary burrower) can home to artificial burrows and if so, whether their homing abilities differ. The two species of crayfish, Orconectes rusticus and Fallicambarus fodiens, were examined for their ability to home to artificial burrows in a laboratory setting. Animals were placed in a homing arena, motivated to search by the presence of food, and subsequently return to the burrows. The movements of each individual crayfish were digitized and analyzed for changes in walking speed, velocity and heading angle relative to burrows, total distance travelled and path turning angles. Crayfish of both species successfully returned home, although F. fodiens had a higher homing success rate than O. rusticus. Detailed kinematic analysis showed that walking speeds almost doubled during homing to burrows and heading angles were significantly closer to zero than on the outward journeys for both species. Path turning angles were significantly lower for O. rusticus than for F. fodiens. These findings indicate that these species of crayfish can successfully home without the visual landmark of burrow chimneys and that the primary burrower (F. fodiens) appears to be more successful with straighter return paths. The differences in these two species to home and the underlying mechanisms of homing may be due to the differences in burrow use with primary burrowers showing more efficient homing than tertiary burrowers.